2021
DOI: 10.1111/dpr.12573
|View full text |Cite
|
Sign up to set email alerts
|

Why are aid projects less effective in the Pacific?

Abstract: Motivation The Pacific is the world’s most aid‐dependent region, yet available data suggest aid projects are less effective on average in the Pacific than elsewhere in the developing world. Purpose This article examines the most likely explanations for lower aid project effectiveness in the Pacific. Explanations include poor governance, restricted levels of political freedom, poor economic performance, isolation, and small populations. Methods and approach Three approaches to causal mediation analysis are used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The issue of geo‐strategic distraction, is seemingly more and more inevitable in the current context of escalating geo‐strategic insecurity, and which underpins Australia's defence discourses. This further undermines the effectiveness of aid and development in the Pacific, because interests tend to be weighted with “mixed motives,” as Wood et al (2022, p. 21) aptly put it. An example would be Fiji's Black Rock military and defence facility, which was rebranded by the Australian government as a Peacekeeping and Humanitarian Assistance & Disaster Relief Camp, after the Chinese had demonstrated keen interest in supporting the development of such a camp (Ivarature, 2023; Tarte, 2021).…”
Section: Pacific Development: Engagement and Entanglements?mentioning
confidence: 99%
See 2 more Smart Citations
“…The issue of geo‐strategic distraction, is seemingly more and more inevitable in the current context of escalating geo‐strategic insecurity, and which underpins Australia's defence discourses. This further undermines the effectiveness of aid and development in the Pacific, because interests tend to be weighted with “mixed motives,” as Wood et al (2022, p. 21) aptly put it. An example would be Fiji's Black Rock military and defence facility, which was rebranded by the Australian government as a Peacekeeping and Humanitarian Assistance & Disaster Relief Camp, after the Chinese had demonstrated keen interest in supporting the development of such a camp (Ivarature, 2023; Tarte, 2021).…”
Section: Pacific Development: Engagement and Entanglements?mentioning
confidence: 99%
“…The Pacific region houses 10 of the world's most aid supported countries (Wood et al, 2022). Australia is responsible for 43% of all Pacific aid (Lowy Institute, 2023), but other significant multilateral organizations such as the World Bank, the Asian Development Bank and other countries have a significant imprint in the region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a first-of-its-kind study, Wood et al (2020) address the problems of aid project effectiveness in the Pacific by using causal mediation analysis of aid effectiveness at the project level. Utilizing statistical analysis of project level performance, they find that the "remoteness and small populations of many Pacific countries appear to be the main constraint on aid effectiveness in the region" and identified that "on average, the countries of the Pacific are better governed and freer than the rest of the developing world (at least as captured in standard measures)," which they conclude is linked with diminished effectiveness of aid (2020, 13).…”
Section: Beneath the Blue Pacific-the Currentsmentioning
confidence: 99%
“…The provision of water and sanitation services in Pacific Island countries (PICs) is among the lowest in the world—only half of the population use improved drinking water sources and only a third use improved sanitation (WHO, 2016). An added challenge is that aid projects in the PICs are regarded as less effective than other parts of the world (Wood et al, 2021). In Solomon Islands, despite efforts by the government and aid organizations, the provision of sustainable and appropriate water, sanitation, and hygiene (WASH) services remains poor.…”
Section: Introductionmentioning
confidence: 99%